Animasi Edukasi Serangga Penyengat bagi Anak 6-9 Tahun dengan Pendekatan Karakter Antropomorfisme - Tito Maulana; Nugrahardi Ramadhani; Didit Prasetyo (Rekam, 2025)
Educational Animation on Stinging Insects for Children Aged 6–9 Using an Anthropomorphic Design Approach. The global decline in insect populations has become a pressing environmental concern. Studies predict a 40% decrease in the coming decades due to habitat loss, pollution, and climate change. Among the most affected are stinging insects from the order Hymenoptera, such as ants, bees, and wasps. Despite their essential ecological roles, these insects are often perceived as pests due to their painful stings. Educational efforts are therefore needed, particularly for children aged 6–9, through engaging media such as educational animation. An anthropomorphic approach has been shown to effectively attract children's attention and raise awareness of stinging insects.The design process involved literature review on child development, stinging insect biology, anthropomorphic character design, and animation production. This was followed by analysis of existing anthropomorphic animations, in-depth interviews with entomologists and children’s animation experts, and iterative qualitative analysis. The animation was then tested with children aged 6–9 years old. The final product, an animation titled Exploring Entopia, successfully captured children’s interest and improved their knowledge of stinging insects by 68% after viewing. This outcome highlights the potential of anthropomorphic animation as a reference for developing science education media at the elementary level.